Perlindungan Konsumen Atas Kesalahan Pengiriman Barang Dalam Transaksi Jual Beli Online Pada Shopee (Hukum Perdata) - Gilang Bagaskara; Grasia Kurniati (Peneliti.net, 2023)
This study aims to explain Shopees efforts to protect consumers against shipping errors in online buying and selling transactions on Shopee e-commerce and the type of consumer protection for shipping errors in online buying and selling transactions. According to the findings of the research, online sales and purchases frequently involve errors in delivery as well as goods that do not meet the promised specifications. UUPK regulates consumer protection without harming business actors. According to Article 9 of the ITE Law, business actors offering products via electronic systems are also required to provide accurate and complete information regarding the terms of the contract, the business actors, and the products. The principles that parties to electronic transactions must take into account are outlined in Article 3 of the PP on Trading Through Electronic Systems. Situational and individual factors are the two reasons why business actors send consumer goods in the wrong way. Despite the fact that consumers frequently contribute to shipping errors due to their own inaccuracies. The current Shopee terms of use, which Shopee has prepared and is in accordance with UUPK provisions and does not conflict with Indonesian laws, contain Shopees efforts to safeguard customers and business actors. The government should be asked to make changes to the UUPK by adding articles about rights, responsibilities, sanctions, and consumer protection in online buying and selling transactions. As a service provider, Shopee should be more selective in registering sellers who will join the platform because business actors continue to make numerous delivery errors.